MODEL PENGAWASAN PEMBELAJARAN PENDIDIKAN JASMANI - Yudha M. Saputra, - (2008)
The background of this study is related to the poor performance of elementary school physical education teachers. Teacher's performance is much influenced by supervision service. With the support of supervision, the performance of physical education teachers can be improved. Related to these central issues it is shown that supervision services in the field do not have a model which can accommodate all of supervision components. However the main focus of supervision is an administrative function. The development of supervision model is one of the steps to optimize the function of principals and supervisors. In this study, supervision model focuses on physical education teachers in elementary school. According to theory, the improvement of teachers' performance must be done by considering the internal and external factors of the teachers. Supervision aids the teachers in improving instructional condition. Supervision is one of activities to help and serve teachers in order to increase the ability and quality of their instructions. Optimal application of supervision model can be used to improve teacher's performance The method used in this study was research and development cycles. There are three stages followed: (1) finding out the previous studies, (2) developing the result based on the finding, and (3) trying out the model and revising it The research and development cycle can be repeated until the result in the field showed that the result fulfill objectivity level. The result of this study showed that there are three findings as follows: (1) the implementation of supervision used for administrative function, (2) elements of supervision development model consist of pre, implementation, and post, and (3) with using sample 20 teachers and 200 students of elementary school has proved that the development supervision model is effective to improve the quality of physical education teacher's performance and student's achievement. The conclusion of this study is that the development of supervision model in physical education instructional has influenced significantly upon the performance of physical education teachers in elementary school. According to this study it is shown that this model is effective to improve the quality of teacher's performance and student's achievement.